Do combination HIV prevention programmes result in increased empowerment, inclusion and agency to demand equal rights for marginalised populations in low-income and middle-income countries? A systematic review - Marija Pantelic; Siyan Yi; Carinne Brody; Say Sok; Sovannary Tuot; Enrique Restoy (BMJ Global Health)
Introduction This systematic review aims to determine if combination HIV prevention programmes include outcome measures for empowerment, inclusion and agency to demand equal rights and measure the relationship between empowerment and HIV prevention outcomes.Methods An electronic literature search of PubMed, POPLINE, Index Medicus and Google Scholar was conducted between August and October 2018. We included studies that evaluated combination prevention programmes that had all three types of intervention components and that specifically serve members of populations disproportionately affected by HIV published from 2008 to 2018. The selected studies were screened for inclusion, and relevant data abstracted, assessed for bias and synthesised.Results This review included a total of 15 studies. Findings indicate that combination HIV prevention programmes for marginalised populations have delivered a variety of theory-based behavioural and structural interventions that support improvements in empowerment, inclusion and agency. However, empowerment, inclusion and least of all agency are not measured consistently or in a standardised way. In addition, analysis of their relationships with HIV prevention outcomes is rare. Out of our 15 included studies, only two measured a relationship between an empowerment, inclusion or agency outcome and an HIV prevention outcome.Conclusion These findings suggest that policy-makers, programme planners and researchers might need to consider the intermediate steps on the pathway to increased condom use and HIV testing so as to explain the ‘how’ of their achievements and inform future investments in HIV prevention. This will support replication and expansion of programmes and ensure sustainability of the programmes.PROSPERO registration number CRD42018106909